2005
DOI: 10.1002/hep.20886
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Expression of ABC Transporters G5 and G8 Does Not Correlate With Biliary Cholesterol Secretion in Liver Transplant Patients *

Abstract: The adenosine triphosphate (ATP)-binding cassette (ABC)-transporters ABCG5 and ABCG8 have been shown to mediate hepatic and intestinal excretion of cholesterol. In various (genetically modified) murine models, a strong relationship was found between hepatic expression of ABCG5/ABCG8 and biliary cholesterol content. Our study aimed to relate levels of hepatic expression of ABCG5 and ABCG8 to biliary excretion of cholesterol in man. From 24 patients who had received a liver transplant, bile samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…18,21,26 However, there is residual biliary cholesterol secretion in Abcg5 or Abcg8 knockout mice, 18,21,26 and previous studies involving our group have shown that Abcg5/Abcg8-independent biliary cholesterol secretion occurs. [21][22][23] Based on the results of this study, we would propose that SR-BI acts as a key candidate for mediating this Abcg5/Abcg8-independent fraction of biliary cholesterol secretion. As evidenced by the correction of the biliary cholesterol secretion deficit of Abcg5 knockout mice by hepatic SR-BI overexpression, SR-BI can drive biliary cholesterol secretion independent of Abcg5.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…18,21,26 However, there is residual biliary cholesterol secretion in Abcg5 or Abcg8 knockout mice, 18,21,26 and previous studies involving our group have shown that Abcg5/Abcg8-independent biliary cholesterol secretion occurs. [21][22][23] Based on the results of this study, we would propose that SR-BI acts as a key candidate for mediating this Abcg5/Abcg8-independent fraction of biliary cholesterol secretion. As evidenced by the correction of the biliary cholesterol secretion deficit of Abcg5 knockout mice by hepatic SR-BI overexpression, SR-BI can drive biliary cholesterol secretion independent of Abcg5.…”
Section: Discussionmentioning
confidence: 83%
“…19 However, in the absence of Abcb4, even high-level overexpression of Abcg5/Abcg8 does not increase biliary cholesterol secretion, 20 delineating the crucial role for biliary phospholipids in mixed micelles with bile salts as acceptors for cholesterol solubilization. Importantly, an Abcg5/Abcg8-independent cholesterol secretion pathway has been described; [21][22][23] however, the mediator of this process remains unknown.…”
mentioning
confidence: 99%
“…The dimer formed by the half transporters ABCG5 and ABCG8 is the primary efflux mechanism for unmodified cholesterol from cells of the small intestine and the liver. Deletion of ABCG5 and ABCG8 does not completely ablate cholesterol efflux suggesting that a secondary mechanism for the removal of cholesterol may exist in mice 3,4 , with confirmatory findings in humans 5 .…”
Section: Introductionmentioning
confidence: 81%
“…ABCG 5/ABCG8 may not be rate-limiting, because parents of sitosterolemic patients have no biochemical phenotype under physiological conditions, although they must have halfnormal functioning sterolins. In this context, a recent study of ABCG5/ABCG8 expression in liver transplant patients found no correlation between mRNA expression of these transporters and biliary cholesterol secretion (sitosterol secretion was not reported) [13].…”
Section: Function Of Abcg5 and Abcg8mentioning
confidence: 91%